Genome-wide identification, phylogenetic and expression pattern analysis of MADS-box family genes in foxtail millet (Setaria italica) - Dili Lai; Jun Yan; Ailing He; Guoxing Xue; Hao Yang; Liang Feng; Xiaobao Wei; Long Li; Dabing Xiang; Jingjun Ruan; Yu Fan; Jianping Cheng (Scientific Reports, 2022)
Abstract Foxtail millet (Setaria italica) is rich in nutrients and extremely beneficial to human health. We identified and comprehensively analyzed 89 MADS-box genes in the foxtail millet genome. According to the classification of MADS-box genes in Arabidopsis thaliana and rice, the SiMADS-box genes were divided into M-type (37) and MIKC-type (52). During evolution, the differentiation of MIKC-type MADS-box genes occurred before that of monocotyledons and dicotyledons. The SiMADS-box gene structure has undergone much differentiation, and the number of introns in the MIKC-type subfamily is much greater than that in the M-type subfamily. Analysis of gene duplication events revealed that MIKC-type MADS-box gene segmental duplication accounted for the vast majority of gene duplication events, and MIKC-type MADS-box genes played a major role in the amplification of SiMADS-box genes. Collinearity analysis showed highest collinearity between foxtail millet and maize MADS-box genes. Analysis of tissue-specific expression showed that SiMADS-box genes are highly expressed throughout the grain-filling process. Expression analysis of SiMADS-box genes under eight different abiotic stresses revealed many stress-tolerant genes, with induced expression of SiMADS33 and SiMADS78 under various stresses warranting further attention. Further, some SiMADS-box proteins may interact under external stress. This study provides insights for MADS-box gene mining and molecular breeding of foxtail millet in the future.